2017
DOI: 10.1186/s12864-017-4173-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and population structure of maize inbred lines adapted to the mid-altitude sub-humid maize agro-ecology of Ethiopia using single nucleotide polymorphic (SNP) markers

Abstract: BackgroundMolecular characterization is important for efficient utilization of germplasm and development of improved varieties. In the present study, we investigated the genetic purity, relatedness and population structure of 265 maize inbred lines from the Ethiopian Institute of Agricultural Research (EIAR), the International Maize and Wheat Improvement Centre (CIMMYT) and the International Institute of Tropical Agriculture (IITA) using 220,878 single nucleotide polymorphic (SNP) markers obtained using genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
52
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 39 publications
13
52
1
Order By: Relevance
“…Average genetic distance reported was 0.37 which is comparable with the earlier findings [26][27][28]. Masuka et al, [26] reported distances ranging from 0.004 to 0.40 with a mean of 0.294 from the analysis of 53 parental lines and two F 2 populations derived from the CIMMYT Africa breeding program.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Average genetic distance reported was 0.37 which is comparable with the earlier findings [26][27][28]. Masuka et al, [26] reported distances ranging from 0.004 to 0.40 with a mean of 0.294 from the analysis of 53 parental lines and two F 2 populations derived from the CIMMYT Africa breeding program.…”
Section: Discussionsupporting
confidence: 81%
“…Beyene et al, [27] analyzed the genetic distances of 703 doubled haploids and reported distances ranging from 0.070 to 0.457 with an average of 0.355. Ertiro et al, [28] reported genetic distances which ranged from 0.011 to 0.346 with an average of 0.313 across pairwise combinations of 265 inbred lines. For Beyene et al, [27] most of the distances fell between 0.300 to 0.475 with a frequency of 69% and in addition, less than 5% of the distances fell below 0.10.…”
Section: Discussionmentioning
confidence: 99%
“…DAPC analysis divided the BSPG into four subpopulations (Fig 2), and this result was confirmed by the NJ phylogram of the SM distance of the whole population (Fig 3). To obtain the population structure, some studies have reported similar or better results for DAPC analysis than for the Bayesian model-based method [63,8587] implemented in STRUCTURE software [88–90]. In addition, for complex genomes, several assumptions are not fulfilled with the use of STRUCTURE; therefore, the applicability of this algorithm may be limited in sugarcane [34,37,38,91].…”
Section: Discussionmentioning
confidence: 99%
“…It is helpful for genotyping without prior knowledge about the genome of the species and is useful for exploring plant genetic diversity on a genome-wide scale [4]. In the last few years, GBS has been used to investigate the genetic diversity of many crop species, including maize, rice, barley, tomato, wheat, sorghum, soybean, watermelon and Capsicum [2128].…”
Section: Introductionmentioning
confidence: 99%